Media Responsibility During the Coverage of Terrorist Attacks – A Case Study of the Abduction and Execution of the Croatian Citizen Tomislav Salopek Era - Branimir Felger; Gordana Lesinger (Communication Today, 2025)
The authors provide an overview of the relations between terrorist atrocities and media coverage of the said atrocities through the analysis of media content present on Croatian Internet portals and national television in the case of terrorist abduction of a Croatian citizen Tomislav Salopek. The study was conducted via a qualitative discursive analysis. The authors focus on both identifying elements and reasons of the media coverage of that case as well as on their impact on the public. Also, the authors try to emphasise the historically important difference in interpretation of the definition of terrorism, especially in today’s context of advanced media technology and the phenomenon of live reporting on the events. For the purpose of understanding the impact terrorist activities have on government policy and especially on the psychological state of the public and the victims’ families, the authors pay particular attention to the ethical and legal standards when reporting on acts of terrorism.